Implementation of Pharmaceutical Care in Geriatrics: Strategies Adopted and Experiences Acquired - de Oliveira, Alan Maicon; Falaschi Romeiro, Barbara; Vilela Rodrigues, João Paulo; Silveira de Almeida Campos, Marília; Rossi Varallo, Fabiana; Régis Leira Pereira, Leonardo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To describe the steps, strategies adopted, and experiences accumulated during the implementation of pharmaceutical care in a geriatric ward. Method: A descriptive mixed-methods study was proposed, carried out in three planned stages for the implemen tation of pharmaceutical care (medication reconciliation, medication review, and phar macotherapeutic follow-up) in a geriatric ward at the University of São Paulo Hospital. In the first stage, a scoping review was conducted using the EMBASE, Web of Science, and PubMed databases. The second stage consisted of developing a situational diagnosis of the ward and adjusting procedures. The third stage comprised an intervention method aimed at identifying and resolving drug-related problems and analyzing associated clinical outcomes. Results: In the first stage, after screening 3,640 articles on pharmaceutical interventions in geriatrics, 35 were included in the review. The interventions frequently used the STOPP/START criteria and the Beers criteria. The main barriers were the lack of specific training and restrictions on service continuity. This stage provided scientific support for project development. In the second stage, the situational diagnosis addressed the ward’s structure and epidemiological profile. Pharmaceutical services were validated by a multidisciplinary team and well accepted. In the third stage, 88% of patients had at least one PRP, with an average of 1.4 PRPs per patient. The acceptance rate of pharma ceutical recommendations was 85%. Conclusion: The planned method was effective in implementing pharmaceutical care, with the creation of informative materials and eviden ce-based strategies. Considering the context of geriatric wards, this initiative stands out as an innovation in a Latin American country and can serve as a model for similar initiatives.